Air contaminants, ventilation, and industrial hygiene economics the practitioner's toolbox and desktop handbook - Wabeke, Roger L. (Taylor & Francis, 2013)
"This book provides industrial hygienists with a reference containing the equations, conversions, and formulas they encounter in their day-to-day duties. Containing 725 unique problems and solutions, the book is a study aid to those taking the certification exams (CIH, CSP, CHMM, and DABT). It also includes 154 business economic case studies demonstrating how to preserve your clients' financial resources, promote industrial hygiene, foster worksite safety, learn the financial ropes of business economics, and help control your clients' potential adverse environmental impact and, in so doing, greatly enhance career progress"-- Provided by publisher.
Keywords: Industrial safety -- Handbooks, manuals, etc.; Environmental engineering -- Handbooks, manuals, etc.; Industrial hygiene -- Handbooks, manuals, etc.; Air -- Purification -- Handbooks, manuals, etc.; Ventilation -- Handbooks, manuals, etc.; Industrial toxicology -- Handbooks, manuals, etc.; Work environment -- Economic aspects -- Handbooks, manuals, etc.; elektronické knihy; electronic books